Technology Business Incubator Service Challenges During the Covid-19 Pandemic: Traditional Incubator Versus Virtual Incubator - Setiowiji Handoyo; Uus Faizal Firdaussy; Siti Kholiyah (Wacana Journal of Social and Humanity Studies, 2021)
Technology business incubator (TBI) is an institution that has an essential role in supporting the creation and development of entrepreneurship in the early stage of their business life cycle. The Covid-19 pandemic made the incubator service put on hold due to the government's social restriction policy to deal with the Sars-CoV-2 spreading. Virtual incubator services become a new model for delivering incubator services during the Covid -19 pandemic due to traditional incubator services is not suitable yet impossible to be held. The research aims to analyse an incubator service model in the pandemic, identify the virtual incubator services' weakness during the Covid-19 pandemic, and formulate a policy recommendation to cope with incubator services problems, either traditionally or virtually. The research was conducted from July 2019 to October 2020 by using a qualitative descriptive research method with the TBI PPII LIPI as a case study. Data collection will carry out through observation, interviews, documentation, and discussion record archive. The framework uses best practices in incubator services. The research findings show that IBT services that only use one of the two existing IBT models are not the right choice during the Covid-19 pandemic. Both Incubator models each have limitations. Hence, this research offers a hybrid incubator service model that combines traditional and virtual incubator services.